(untitled) (Cadernos de Sociomuseologia, 2024)
The article discusses the project Mining the Museum, created in 1992 by artist Fred Wilson (1954 -) at the Maryland Historical Society. The goal is to identify how artistic interventions can help to indicate new pathways for historical and ethnographic museums committed to more just heritage practices. The discussion departs from the article “Museums in the Colonial Horizon of Modernity: Fred Wilson’s Mining the Museum (1992)” written by Walter Mignolo, and proposes a broader perspective to understand Wilson’s work as an institutional and community intervention, not just as an exhibition. Mignolo’s interpretation is juxtaposed with contributions by Silvia Rivera Cusicanqui and Maurice Halbwachs, who insisted on the collective construction of knowledge and on the importance of combining theory and practice. The article concludes that Mining the Museum presents three possible routes for artistic interventions in museums: the first route runs from the institution outwards; the second, inwards to the institution; and the third, within the institution. Keywords: Museum Studies, Contemporary Art, decoloniality